The role of organizational learning and resilience for change in building quality improvement capacity in primary care - Schuttner, Linnaea (Health Care Manage Rev, 2021)
BACKGROUND: The extent that organizational learning and resilience for the change process, i.e. adaptive reserve, is a component of building practice capacity for continuous quality improvement is unknown. PURPOSE: To examine the association of adaptive reserve and development of quality improvement capacity. METHODOLOGY: 142 primary care practices were evaluated at baseline and 12 months in a randomized trial to improve care quality. Practice adaptive reserve (AR) was measured by staff survey along with a validated quality improvement capacity assessment (QICA). We assessed the association of baseline QICA with baseline AR, and both baseline and change in AR with change in QICA from 0-12 months. Effect modification by presence of QI infrastructure in parent organizations and trial arm were examined. RESULTS: Mean QICA increased from 6.5 to 8.1 (P <0.001) and mean AR increased from 71.8 to 73.9 points (P <0.001). At baseline, there was a significant association between AR and QICA scores: the QICA averaged 0.34 points higher (95% CI 0.04-0.64, P =0.03) per 10-point difference in AR. There was a significant association between baseline AR and 12-month QICA – which averaged 0.30 points higher (95% CI 0.02-0.57, P =0.04) per 10-points in baseline AR. There was no association between changes in AR and the QICA from 0-12 months, and no effect modification by trial arm or external QI infrastructure. CONCLUSIONS: Baseline AR was positively associated with both baseline and follow-up QI capacity, but there was no association between change in AR and change in the QICA, suggesting AR may be a precondition to growth in QI capacity. PRACTICE IMPLICATIONS: Findings suggest that developing AR may be a valuable step prior to undertaking QI-oriented growth, with implications for sequencing of development strategies, including added gain in quality improvement capacity development from building AR prior to engaging in transformation efforts.